2022
DOI: 10.1038/s41416-022-01819-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of circulating tumour cells: the KEY to understand the biology of the metastatic cascade

Abstract: Metastasis formation is the main cause of cancer-related death in patients with solid tumours. At the beginning of this process, cancer cells escape from the primary tumour to the blood circulation where they become circulating tumour cells (CTCs). Only a small subgroup of CTCs will survive during the harsh journey in the blood and colonise distant sites. The in-depth analysis of these metastasis-competent CTCs is very challenging because of their extremely low concentration in peripheral blood. So far, only f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 91 publications
(105 reference statements)
0
39
0
Order By: Relevance
“…Further, it would also be interesting to investigate whether circulating tumor cells of ctDNA-positive stage II CRCs correlates with a TFunctionalProg high-risk subgroup, and this may help the understanding of the functionality and the origin of heterogenous circulating tumor cells. [31] TFunctionalProg utilize standard FFPE slides that can be stored at room temperature and provides an alternative to ctDNA-based prognostic biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it would also be interesting to investigate whether circulating tumor cells of ctDNA-positive stage II CRCs correlates with a TFunctionalProg high-risk subgroup, and this may help the understanding of the functionality and the origin of heterogenous circulating tumor cells. [31] TFunctionalProg utilize standard FFPE slides that can be stored at room temperature and provides an alternative to ctDNA-based prognostic biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Besides their value as diagnostic markers, the analyses of CTCs in patients with cancer (and experimental models) can contribute to understand the complexity of metastatic spread which may eventually lead to a favorable outcome of patients with solid malignancies. 10 In this context, mathematical modeling might help to encompass the complex process of the metastatic cascade. Dujon et al used simulations (adaptation of the Drake equation) based on published breast cancer data and demonstrated that the survival of CTCs in the bloodstream is a key step in the complex process of the metastatic cascade.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these models provide insights into CTC biology and in particular might help to identify pathways specific for metastasis-competent CTCs, discover new CTC markers and unravel mechanisms of drug resistance of these CTCs. 10…”
Section: Introductionmentioning
confidence: 99%
“…Besides factors such as shear stress and anoikis, several studies suggest that CTCs survival might be hindered by mechanisms of immune-mediated clearance (8,16). Research interest in understanding the interplay between CTCs and circulating immune cells is growing as it holds great promise to understand the process of metastasis, predict patients' outcome and pave the way for new treatment strategies (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%